2016
DOI: 10.1155/2016/7937696
|View full text |Cite
|
Sign up to set email alerts
|

A High Rated Solar Water Distillation Unit for Solar Homes

Abstract: India is presently focusing on complete utilization of solar energy and saving fossil fuels, which are limited. Various solar energy systems like solar cookers, solar water heaters, solar lanterns, solar PV lights, and solar lamps are continuously availing by the people of India at a low cost and on good subsidies. Apart from this, India is a solar energy promising country with a good number of solar homes (carrying solar energy systems) in its various locations. The present paper focuses on a unique combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The fluctuations of the absorber temperatures are smooth. This phenomenon was also attained by Mirmanto (2003), Saxena and Deval (2016). For the three types of absorbers indicate almost the same temperatures, however, type C elevates little bit higher than other absorber temperatures.…”
Section: Resultssupporting
confidence: 63%
“…The fluctuations of the absorber temperatures are smooth. This phenomenon was also attained by Mirmanto (2003), Saxena and Deval (2016). For the three types of absorbers indicate almost the same temperatures, however, type C elevates little bit higher than other absorber temperatures.…”
Section: Resultssupporting
confidence: 63%
“…The results showed an increase in the distillation process in both cases at the lowest costs and that March and April were the best months for production among the months of the year [8]. In 2016, researchers conducted a study in India through the work of a high-energy solar distiller to distill water in homes and benefit from it in daily needs, The results showed that the daily productivity of distilled water is about (3.66L/day) in the hours of sunshine complete [9]. In 2017, researchers conducted an experimental study on a solar device still using a collection box with an open area for water distillation (1 * 0.6) m, The obtained results showed that the amount of distilled water increases with the increase in the amount of solar radiation and higher.…”
Section: Introductionmentioning
confidence: 99%
“…n number of years, i equals 12% OMC = 0.15 * (AC s ) ………...………………(9) ASV = S * (SFF) ………….…………..….…(10) ASV is the annual salvage value, S is 10% of the total cost Cs, SFF is the capital dumping factor and is given by the following equation:………………..…..…….…(11)The results show in Figure(5) a decrease in the total cost of producing one liter of distilled water from (17.88 IQD) in the first year to (2.15 IQD) after 20 years, and the cost of producing one liter of irrigation water decreases from (9 IQD) in the first year, to (1.07 IQD) at the end of the estimated period for the end of the project, after it cost annually approximately (13,000 IQD/dunam)(8.733 $).…”
mentioning
confidence: 99%